Pengaruh Bimbingan dan Konseling terhadap Tingkah Laku Peserta Didik Kelas XI MIA di MA Al-Muslimun Kawistolegi Karanggeneng Lamongan - Hasyim; Zaini Miftah; Melysiana Yufitamala (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
Educators are not only required to educate students in the intellectual realm, but must also educate in the realm of attitudes (behavior). In controlling the attitudes (behavior) of students in the school environment, there are services, namely Guidance and Counseling (BK). The purpose of this study was to determine: the material of guidance and counseling at MA Al-Muslimun Kawistolegi Lamongan, the behavior of class students, the influence of guidance and counseling on the behavior of class XI MIA students at MA Al-Muslimun. This research was quantitative correlative type, the research population was 47. The data collection technique used online and offline questionnaires, documentation methods, and interview methods (support). The validity test of the instrument used the Pearson product moment, while the reliability test used the Sperman Brown technique of halving. Data analysis using percentage formula and product moment correlation. The results showed that the guidance and counseling materials at MA Al-Muslimun Kawistolegi were good. The students' behavior is also in a good range. Guidance and Counseling have an influence on the behavior of students of class XI MIA at MA Al-Muslimu with a moderate level of significance